2021
DOI: 10.1016/j.ekir.2021.03.877
|View full text |Cite
|
Sign up to set email alerts
|

On Path to Informing Hierarchy of Eplet Mismatches as Determinants of Kidney Transplant Loss

Abstract: Introduction: To mitigate risks related to human leukocyte antigen (HLA) incompatibility, we assessed whether certain structurally defined HLA targets present in donors but absent from recipients, known as eplet mismatches (EMM), are associated with death-censored graft failure (DCGF).Methods: We studied a cohort of 118,313 American 0% panel reactive antibodies (PRA) first kidney transplant recipients (2000 to 2015) from the Scientific Registry of Transplant Recipients. Imputed allelelevel donor and recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…The rationale for this explicit and precise definition of eplets and reactivity patterns also follows from the need to define the most immunogenic eplets in transplantation (56). Multiple studies have tried to identify the most immunogenic eplet mismatches (16,(57)(58)(59), which is a crucial step in making eplet-matching in transplantation clinically applicable. Currently, these studies are limited by the use of different versions of the HLA Epitope Registry and/or HLAMatchmaker and consequently the different eplet definitions that are used in the analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for this explicit and precise definition of eplets and reactivity patterns also follows from the need to define the most immunogenic eplets in transplantation (56). Multiple studies have tried to identify the most immunogenic eplet mismatches (16,(57)(58)(59), which is a crucial step in making eplet-matching in transplantation clinically applicable. Currently, these studies are limited by the use of different versions of the HLA Epitope Registry and/or HLAMatchmaker and consequently the different eplet definitions that are used in the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, as eplets have been theoretically defined, their clinical relevance needs to be validated by antibody verification (8,15). Although antibody-verified eplet mismatches have been demonstrated to correlate with DSA formation and graft survival (13,14), recent reports also indicated that there are still clinically relevant eplets which have not been antibodyverified yet (13,16).…”
Section: Introductionmentioning
confidence: 99%
“…Imputation of 2 field HLA typing is an unavoidable necessity when collating a dataset of sufficient size and with adequate duration of follow-up to address the question of the clinical relevance of individual eplet mismatches, yet this will inevitably impact the reliability of attributing the observed associations to specific eplets, particularly when the authors were unable to determine mismatches at -DRB3/4/5, -DQA, -DPA, and DPB. Mohammadhasanzadeh and colleagues 7 readily acknowledge this limitation of their work and conclude that although their findings require validation from diverse populations with allele-level genotypes before they can be used in prioritizing donor-recipient matching that avoid higher-risk eplet mismatches, they offer a short list of candidate eplet mismatches that could be studied to understand the properties that confer an increased risk of graft failure.…”
mentioning
confidence: 99%
“…In modeling the complex interrelatedness of eplet mismatches through network analysis, they highlight important limitations in simply adding the number of individual eplet mismatches in risk stratification when antibody formation may be targeted at the most immunogenic eplet of a larger eplet cluster or group. Ultimately, in demonstrating a hierarchy of risk associated with specific eplet mismatches, Mohammadhasanzadeh and colleagues 7 question the validity of quantitative eplet mismatch loads as a tool for assessing risk at the time of organ allocation, where each eplet mismatch is considered to hold equal weight.…”
mentioning
confidence: 99%
See 1 more Smart Citation